2003
DOI: 10.1165/rcmb.4908
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase-Activated Receptor-2 and Human Lung Epithelial Cells

Abstract: Proteinase-activated receptor (PAR)-2 is cleaved within its aminoterminal extracellular domain by serine proteinases such as trypsin, unmasking a new aminoterminus starting with the sequence SLIGKV, which binds intramolecularly and activates the receptor. PAR-2 has been reported to be involved in inflammation within the lungs. We show that PAR-2 is expressed not only by human alveolar (A549), but also by bronchial (16HBE) epithelial cell lines, using RT-PCR and flow cytometry with a PAR-2 antibody whose epitop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 40 publications
6
85
0
Order By: Relevance
“…Because elastase cleaves PAR 2 distal to the trypsin cleavage site, elastase pretreatment can prevent subsequent activation by trypsin, and thereby "disarm" the receptor (49,56). We found that pretreatment with elastase prevented trypsin signals in oocytes, which confirms this mechanism.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Because elastase cleaves PAR 2 distal to the trypsin cleavage site, elastase pretreatment can prevent subsequent activation by trypsin, and thereby "disarm" the receptor (49,56). We found that pretreatment with elastase prevented trypsin signals in oocytes, which confirms this mechanism.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies using immunofluorescence and confocal microscopy suggest that whereas trypsin-activated PAR 2 undergoes endocytosis, elastase-activated PAR 2 remains at the plasma membrane (32,49). To quantitatively assess PAR 2 trafficking at the plasma membrane, we measured the BRET signal between PAR 2 -RLuc8 and two proteins that reside at the plasma membrane: KRas-Venus, which is present in cholesterol-independent microdomains (50), and RIT-Venus, which is uniformly distributed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such cleavage may prevent receptor activation by amputating or destroying the tethered ligand, depending upon the site where the additional cleavage occurs. Chymotrypsin is known to disable PAR-1 (Vouret-Craviari et al, 1995), cathepsin G can disable PAR-1 and PAR-2 (Molino et al, 1995;Dulon et al, 2003;Sokolova et al, 2005), and bacterial metalloprotease thermolysin was shown by us to disable PAR-2 in HBE and A549 cells (Ubl et al, 2002). We have tested the possibility for mesotrypsin to act as a disabling protease.…”
Section: Discussionmentioning
confidence: 96%
“…24 Fungi control secretory responses of PMNs, including protease activity, through TLR signaling. 22,23 Therefore, we hypothesized that fungi, through TLR activation, stimulate the release of proteases from PMNs that cleave PAR 1 and PAR 2 and modulate their activity.…”
Section: Host Proteases Regulate the Expression And Function Of Parmentioning
confidence: 99%